2010
DOI: 10.1016/j.aller.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis, atopy, asthma and ABPA

Abstract: The role of atopy on cystic fibrosis (CF) progression remains unclear but evidence suggests that it may influence the appearance of co-morbid conditions such as CF asthma or allergic bronchopulmonary aspergillosis (ABPA). Recognising asthma in patients with CF is not always easy but the identification of atopic markers favours the diagnosis. Physicians should be aware of this fact in order to achieve a better control of respiratory symptoms in patients with CF. Bronchial mucosa inflammation and abnormal mucus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 85 publications
(107 reference statements)
3
32
0
1
Order By: Relevance
“…A fact that supports this assumption is the significantly higher proportion of pet owners that is sensitized against A. fumigatus compared to the non‐pet owner group. This fits with the higher proportion of pet owners with CF that developed ABPA, as allergic sensitization to A. fumigatus is one of the hallmarks of ABPA diagnosis and precedes development of ABPA . Pathogenic transmission from pet to owners does take place in patients with CF and preliminary results from our group indicated transmission of A. fumigatus from a rodent to a patient with CF .…”
Section: Discussionsupporting
confidence: 78%
“…A fact that supports this assumption is the significantly higher proportion of pet owners that is sensitized against A. fumigatus compared to the non‐pet owner group. This fits with the higher proportion of pet owners with CF that developed ABPA, as allergic sensitization to A. fumigatus is one of the hallmarks of ABPA diagnosis and precedes development of ABPA . Pathogenic transmission from pet to owners does take place in patients with CF and preliminary results from our group indicated transmission of A. fumigatus from a rodent to a patient with CF .…”
Section: Discussionsupporting
confidence: 78%
“…The presence of environmental allergens has been associated with worse respiratory outcomes in other obstructive lung diseases, most notably asthma7 and COPD 8. However, with the exception of allergic bronchopulmonary aspergillosis,9 it remains unclear whether an allergic response to specific environmental exposures leads to increased respiratory morbidities in CF 10, 11. Two studies have demonstrated an association between reduced forced expiratory volume in 1 sec (FEV 1 ) and environmental allergies defined by skin testing(n = 25; P < 0.01; n = 48; P < 0.05) 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Airway obstruction (which is reversible with bronchodilator use), seasonality, induction by allergens, a personal history of atopy (eczema or rhinitis), and a family history of asthma can be useful as predictors of asthma. ( 22 ) …”
Section: Discussionmentioning
confidence: 99%